Performance Improvement of a Centrifugal Compressor by Passive Means - N. Sitaram; S. M. Swamy (International Journal of Rotating Machinery)
The present experimental investigation deals with performance improvement of a low-speed centrifugal compressor by inexpensive passive means such as turbulence generator placed at different positions and partial shroud near the rotor blade tip. The experiments are carried out at three values of tip clearance, namely 2.2%, 5.1%, and 7.9% of rotor blade height at the exit. Performance tests are carried out for a total of 13 configurations. From these measurements, partial shroud is found to give the best performance. The improvement in the compressor performance may be due to the reduction of tip leakage flows by the small extension of partial shroud (2 mm on the pressure surface side). Although there is nominal change in performance due to turbulence generator (TG), TG has beneficial effect of increased operating range.